IMPLEMENTASI ANNEX 17 TENTANG PENGAWASAN KEAMANAN DAN KESELAMATAN PENERBANGAN OLEH AVIATION SECURITY BANDARA SOEKARNO HATTA CENGKARENG JAKARTA - Saifullah, Saifullah; Doddy Mulyono (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
Aviation safety depends on various factors, including the condition of the aircraft, the condition of the flight crew, infrastructure and natural factors, seen as a combination of various aspects such as quality, reliability, availability, stability and security. The problems of this research are: (1) How is Annex 17 implemented? regarding Aviation Security and Safety Supervision by Aviation Security at Soekarno Hattta Cengkareng Jakarta Airport? (2) What are the inhibiting factors in monitoring aviation security and safety by Aviation Security at Soekarno Hatta Cengkareng Airport, Jakarta? The research method used in this research is normative empirical, with primary data and secondary data. Data collection procedures were carried out by conducting literature studies and field studies. The results of the research show, Implementation of Annex 17 concerning Aviation Security and Safety Supervision by Aviation Security at Soekarno Hattta Airport, Cengkareng, Jakarta. carried out through preventive and repressive supervision. Preventive supervision is carried out by conducting outreach activities on aviation safety regulations and to related parties at Soekarno Hatta Cengkareng Airport, Jakarta, determining the operational performance of airport services and air transportation, and coordinating with government agencies and related parties at the airport. Repressive supervision is carried out by monitoring, inspecting and directly assessing all aspects related to aviation safety at Soekarno Hatta Cengkareng Airport, Jakarta.